2013
DOI: 10.1177/0022034513475625
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Pathogen Accelerates Lipid Peroxidation and Atherosclerosis

Abstract: Recent studies have shown an association between periodontal disease and cardiovascular disease. We previously reported that intravenous challenge with Aggregatibacter actinomycetemcomitans (Aa) accelerated atherosclerosis in apolipoprotein E-deficient spontaneously hyperlipidemic (Apoe(shl)) mice. In this study, we investigated whether live cells were required for atherosclerosis induction or whether lipopolysaccharide (LPS) alone was sufficient to increase atherosclerotic damage. Mice were injected intraveno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 29 publications
(36 reference statements)
0
31
0
Order By: Relevance
“…These data suggest that this may be the major mechanism by which periodontal bacteria causally induce atherosclerosis. In support of this finding, it was recently reported that intravenous injection of live Aggregatibacter actinomycetemcomitans bacteria into spontaneously hyperlipidemic mice (KOR-ApoE shl ) promotes the upregulation of TLR gene expression and lipid peroxidation (37). The authors of that study found that increases in the expression levels of ROS-producing enzymes were significant for the response to live bacterial infection but not to heat-killed bacteria, further supporting the notion that viable bacteria are responsible for actively promoting atherosclerotic lesion formation.…”
Section: Gene Group Genementioning
confidence: 69%
“…These data suggest that this may be the major mechanism by which periodontal bacteria causally induce atherosclerosis. In support of this finding, it was recently reported that intravenous injection of live Aggregatibacter actinomycetemcomitans bacteria into spontaneously hyperlipidemic mice (KOR-ApoE shl ) promotes the upregulation of TLR gene expression and lipid peroxidation (37). The authors of that study found that increases in the expression levels of ROS-producing enzymes were significant for the response to live bacterial infection but not to heat-killed bacteria, further supporting the notion that viable bacteria are responsible for actively promoting atherosclerotic lesion formation.…”
Section: Gene Group Genementioning
confidence: 69%
“…Periopathogens and released proinflammatory mediators also contribute to oxidation of LDL phospholipids and their modification to ox-LDL and to modification of HDL-C by reducing the content of cholesterol esters and sphingomyelin as well as molecules of apolipoprotein (apo) A-I, whereas inflammatory HDL-C loses the ability to inhibit LDL oxidation processes [27]. It has been found, that Aggregatibacter actinomycetemcomitans increased the oxidation of LDL-C through oxidative stress involving NADPH oxidase-and myeloperoxidase-derived reactive oxygen species in apolipoprotein E-deficient spontaneously hyperlipidemic (Apoe(shl)) mice [28]. Macrophages in the intima, through phagocytosis of oxidized LDL, are transformed into foam cells.…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous inoculation with A. actinomycetemcomitans, another periodontal pathogen , has also been shown to accelerate atherosclerosis in hyperlipidemic Apoe shl mice (97) . A. actinomycetemcomitans increased serum levels of C-reactive protein, LPS, IL-6, IL-8, TNF-α, and MCP-1.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial DNA was detected in the heart and increased levels of expression of various proatherogenic factors in the aorta were observed including TLR2, TLR4, adhesion molecules, LOX-1, HSP60 and MCP-1. Although live organisms had the largest effect on accelerating atherosclerotic lesion development, heat-killed organisms or A. actinomycetemcomitans LPS, also had a significant effect (97). All treatment groups demonstrated enhanced expression of Toll and nucleotide oligomeric domain like receptors and oxidation of LDL, which could play a role in lesion progression (97).…”
Section: Introductionmentioning
confidence: 99%